Evaluation of the main causes of post-harvest losses of vegetables sold in Santarém, Pará state - Guerra, Antonia Mirian Nogueira de Moura; Costa, Ana Cecília Moura; Ferreira, Júlia Batista Azevedo; Tavares, Paula Raniele Freitas; Vieira, Thaís Silva; Medeiros, Aline Carla de (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2017)
Vegetables are subject to various types of damage after harvest due to inadequate handling and storage, disease and mechanical injury. The objective of this work was to carry out a survey of the main causes of post-harvest losses in peppers, potatoes and onions marketed in the fairsand supermarkets of Santarém, Pará state. The work was conducted in the retail trade, in the following places: Supermarket, Cohab Fair, Old Airport Fair and Mercadão 2000. The damages in the vegetables were evaluated and classified in: physiological, microbiological and mechanical damages. In all the evaluated places all the vegetables presented some damage, that was attributed like responsible of the losses of direct or indirect form. On the onions the main damages were: thick stalk, poorly formed bulbs, flaccid, discolored and sprouted. All the evaluated peppers presented rectangular and green color, the main damages were: crushed, rotted, skinned, burned and attacked by insects, wounded, withered, cracked and poorly formed. Tubers with superficial cuts did not differ among the different locations, but the most frequent damages were the deep cuts and sprouts. These results reveal the need for investment in the structuring of the retail markets to promote the reduction of undesirable losses and financial losses.